A statistical and dynamic analysis of strategic groups in colombian banking (2008)
This work was aimed at identifying the existence of strategic groups in Colombian banking, their stability and relationship with the average performance of the companies so forming them. Their role in analysing business competence/competition within a concrete industrial sector is highlighted.A strategic positioning approach was used; this arose from Industrial Economics and Strategic Management studies emphasising some external factors determining companies' strategic behaviour and their approach towards competence/competition. Static analysis was used for 2004 and another dynamic one (longitudinal) for the 10-year period 1995-2004. The groups were formed via multivariate ANOVA and MANOVA statistical tests (clusters).